Development of Anti-Radicalism Education Model at Miftahul Huda Al-Azhar Pesantren During COVID-19: A Descriptive Study in Banjar, West Java - Dewi Sadiah; Mustofa Mustofa (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to critically examine the development of an adaptive educational model at Miftahul Huda Al-Azhar Islamic Boarding School in maintaining the quality of students (santri) and mitigating the risks of radicalism during the Covid-19 pandemic. The primary focus lies in the synchronization of traditional values with digital disruption, incorporating key concepts such as ideological immunity, religious moderation (Tawasut), and educational crisis management. Adopting a qualitative descriptive method with participant observation and in-depth interviews, the scope encompasses digital curriculum transformation, productive quarantine policies, and cross-sector strategic collaboration in Banjar City. The findings indicate that integrating nationalistic values into digital platforms and reinforcing mental health through intensive counseling effectively counters radical narratives that exploit social vulnerabilities during crises. Critical challenges identified include digital infrastructure disparities and the limitation of physical interaction, which affects spiritual transmission. This study recommends adopting an inclusive blended learning model and strengthening synergy between educational institutions and security agencies as a prototype for national resilience. This research contributes to the discourse on contemporary Islamic education by formulating a pedagogical framework that bridges traditional ideological protection with modern technological flexibility in facing global disruptions.